Characterization of the different species of Fiddler Crabs (Ocyypodidae Genus (Uca) in Barangay Sapa, Miag-ao, Iloilo. - Simborio, Jing Belache
Assessment of the fiddler crabs (Ocypodidae: Genus Uca) was done in an estuarine creek at Barangay Sapa, Miagao. This study aimed to provide baseline information about the different Uca spp. present in Barangay Sapa, Miagao. The two sampling sites were located near households and subjected to garbage and sewage contamination. Transect lines (10.5m) were set on each site with three sampling plots (plot: Area = 50 cm x 50 cm) per transect line. Collections of samples were done twice - December 17, 2003 and September 2, 2004 - a nine month interval sampling., Four species were identified in the area, U. bellator U.coarctata, U. dussmieri and U. lactea. High percentages of U. coarctata were obtained in the second sampling at site 1 and in the two samplings done at site 2 which made it the dominant species. U bellator predominated only on the first sampling in site 1. Female samples were not classified up to the species level due to the difficulty in recognizing morphological differences among them. It was assumed however, that most of the females were from dominant species (U. coarctata). The indices of similarity and dominance varied per site. U. dussmieri was found in site 2 during the second the second sampling in addition to the 3 species which were present in all sampling periods and sites. There exist a strong linear relationship between pollex/manus ratios and carapace breadth for the four species. The z values obtained for each species exhibit strong linear relationships and the values obtained were highly significant (p<0.5). U. dussumieri was composed of the most matured individuals with pollex/manus and propodous/carapace breadth ratios greater than one (>1). That is 50 percent pollex/manus ratio and 100 percent propodous/carapace breadth ratio of its total population was greater than 1. Though U. coarctata was the dominant species, small percentage of mature individuals were obtained. There was high percentage of leptochelous compared to brachychelous individuals. High percentages also of berried females sampled on the second sampling periods for both sites. Berried females found had the usual carapace breadth size range of 4-6.5mm and may reach up to 10mm. For nonberried, the range was between 3-7.5mm. Generally, female samples had a minimum of 2mm and maximum of 3 mm carapace breadth lengths. The male/female ratio obtained for the two sites in the two sampling periods was 2:1.